Foucault : a very short introduction / Gary Gutting. - Gutting, Gary (Very short introductions., 2005)
This work highlights Foucault's life and thought, showing his impact on society, as well as tackling his thoughts on literature, in particular the avant-garde scene; his philosophical and historical work; and his treatment of knowledge and power in modern society.